The Implementation of Turbine Ventilator As An Alternative Power Plant - Suryadi, Aris (ADI Journal on Recent Innovation, 2020)
Indonesia is actively developing the potential for renewable energy as a substitute for depleting fossil energy reserves. Wind energy is clean energy without polling the environment. Wind energy in Indonesia has great potential, but it is still not optimal enough for its utilization. One form of alternative energy that can be utilized as mechanical energy by wind turbines to convert into electrical energy by dc generators. Ventilators that operate for 24 hours function to suck water and, located on the roof of a warehouse, sports hall . Utilization of wind to become electrical energy is designed from the use of a turbine ventilator as a medium to convert wind into motion energy, where the movement of the turbine is continued by pulley and v-belt comparisons to the generator, this generator produces electricity. This research examines how much electrical energy is produced at different wind speeds ranging from 3 to 5.4 m/s. From the tests conducted, the generator rotation, and the lowest voltage is at wind speed of 3 m/s which is 3.6 V. while the generator speed and the highest voltage is obtained if the wind speed is 5.4 m/s which is 10.3 V.